Deficiency of astrocyte CysLT1R ameliorates depression-like behaviors in mice by modulating glutamate synaptic transmission - Liu, Xiao; Tang, Su-Su; Liu, Si-Ming; Zeng, Jie; Chen, Zhi-Gang; Liu, Cai-Hong; Mu, Rong-Hao; Yuan, Dan-Hua; Zhao, Jia-Jia; Hong, Hao; Wang, Hao (Neurobiology of disease, 2022)
Our previous study suggests that hippocampal cysteinyl leukotriene receptor 1 (CysLT1R) could be involved in depression. Herein we hypothesize that CysLT1R may regulate depression by affecting synaptic glutamate cycling based on existence of CysLT1R in the astrocytes that participate in occurrence of depression. We found that CysLT1R expression was significantly increased in the astrocyte of chronic unpredictable mild stress (CUMS)-induced depression-like mice, CysLT1R astrocyte-specific conditional knockout (AcKO) significantly improved depression-like behaviors, as indicated by decreased immobility time in the forced swimming test and tail suspension test and increased sucrose preference in the sucrose preference test, and knockdown of CysLT1R in the astrocyte of dentate gyrus (DG), the region with the most significant increase of CysLT1R in the astrocyte of depression-like mice, produced similar effects. Correspondingly, overexpression of CysLT1R in the astrocyte of DG induced depression-like behaviors in mice. The further study showed that CysLT1R AcKO ameliorated synaptic plasticity impairment, as reflected by increased synapse, LTP and PSD95, and promoted glutamate transporter 1 (GLT-1) expression by inhibiting NF-κB p65 nuclear translocation mediated by β-arestin2 and clatrhin, subsequently decreased glutamate in synaptic cleft and GluN2B on postsynaptic membrane in depression-like mice. The present study also showed that GLT-1 agonist or NF-κB inhibitor ameliorated depressive-like behaviors induced by overexpression of the astrocyte CysLT1R of DG. Our study demonstrated that astrocyte CysLT1R regulated depression by modulating glutamate synaptic transmission, suggesting that CysLT1R could be a potential target for developing novel drugs of anti-depression. •CysLT1R was significantly increased in the astrocyte of DG in depression-like mice.•Overexpression of CysLT1R in the astrocyte of DG induced depression-like behaviors.•CysLT1R AcKO or knockdown in the astrocyte of DG improved depression-like behaviors.•CysLT1R downregulation antidepression is related to synaptic plasticity enhancement.